Contabilidade tributária e planejamento fiscal aplicado à logística - o ICMS no transporte rodoviário de cargas: estudo das alternativas fiscais e contabilização - crédito outorgado versus crédito nas entradas de insumos - um estudo de caso no segmento de transporte rodoviário de valores - Campoi, José Carlos Sanches (2009)
The transportation services are presented as an essential link of the logistic chain and require considerable levels of resources in the process of making goods and services available to the end consumer. This work has applied tax planning to logistics, more specifically, tax planning applied to the ICMS (Value Added Tax on Sales and Services) applicable to transportation services. Goal: To determine the less costly system between the ICMS credit systems generated by the purchases and that of 20% over the ICMS debt seen in the sales. In order to do so, tax planning was applied to the case study of a company within the goods transportation segment and the lower ICMS to be withheld was studied, having analyzed by State of the Country and having discussed the planning relevant variables. It also puts the case study into a context, approaching the tax planning concepts, ICMS legal aspects, logistics, transportation, goods transportation, the right to ICMS credit in both systems and it has presented a research that verifies which system is the most used by the goods transportation segment, and how ICMS credits are accounted for. It has concluded that the 20% granted credit system is the one that is less costly, in all States and months of the period analyzed, resulting in a withholding 10.3% lower in comparison to the other system, given the relevance of the difference variable between the purchases and sales rates in the planning. It has also concluded that the tax planning application enables the transportation operators to adopt, consciously, the best tax practices. It is an attitude that supports the logistic goal of making goods and services available at reasonable costs and the appropriate application of resources in the goods and services flows